2-Methyl-4-(pyridin-2-yl)-3H-1,5-benzodiazepine - Lhoussaine El Ghayati; Youssef Ramli; Ahmed Moussaif; Jamal Koubachi; Mohamed Labd Taha; El Mokhtar Essassi; Joel T. Mague (IUCrData, 2018)
In the title compound, C15H13N3, the seven-membered ring adopts a boat conformation. In the crystal, inversion-related C—H...N hydrogen bonds form dimers, which pack in an alternating fashion.